In vitro antibacterial activity of essential oils from medicinal plants against major fish pathogens in Mediterranean aquaculture - Kolygas, Markos N.; Kostou, Vasiliki; Pappas, Ioannis S.; Karagouni, Evdokia; Toubanaki, Dimitra K.; Bakopoulos, Vasileios; Kotzamanis, Yannis P.; Nathanailides, Cosmas; Athanassopoulou, Fotini (Frontiers in Aquaculture, 2025)
A rise of intensive Mediterranean aquaculture has been associated with vulnerability to bacterial infections, necessitating alternative approaches to conventional antibiotics. This study evaluated the antibacterial and bactericidal activity of essential oils derived from fifteen medicinal plants against four key bacterial pathogens affecting Mediterranean marine aquaculture: Aeromonas veronii biovar veronii, Aeromonas veronii biovar sobria, Vibrio harveyi, and Tenacibaculum maritimum. Essential oils were screened using disc diffusion assays, and the most effective oils—thyme, oregano, cinnamon, and absinthe—underwent further evaluation through broth microdilution methods. Results demonstrated that these four oils exhibited notable inhibitory and bactericidal effects, with thyme and oregano showing the strongest overall activity across multiple pathogens. Notably, this is among the first studies to document the in vitro efficacy of essential oils against Tenacibaculum maritimum, a major pathogen with limited treatment options. The findings support the potential use of selected essential oils as sustainable and natural antibacterial agents in fish health management, contributing to reduced reliance on antibiotics in aquaculture.